Transformasi Pengembangan Sumber Daya Manusia di Era Digital - Ramadhan Ridho Fadlulloh Iswandi; Mudji Kuswinarno (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
The transformation of human resource development (HRD) in the digital era has become an urgent need for companies to remain competitive in the changing business environment. This article discusses the application of technology in HR development, including the importance of e-learning and digital training, as well as the use of data analytics and artificial intelligence (AI) in HR management. While companies face challenges, such as resistance to change, the digital divide, and data security, there are also significant opportunities that can be capitalized on. If HR transformation is successful, companies can achieve higher work efficiency, accelerate innovation, and improve global competitiveness. To achieve these goals, companies need to build an adaptive culture, invest in digital training, address the digital divide, prioritize data security, and leverage data for better decision-making. With the right approach, companies can optimize the potential of their human resources in facing the challenges and opportunities of the digital era.